Euroland: recovery will slowly gain momentum - Klaus-Jürgen Gern; Christophe Kamps; Carsten-Patrick Meier; Frank Oskamp; Joachim Scheide (Institut für Weltwirtschaft (IfW), 2003)
Economic activity in the euro area has weakened since last summer. In the second half of 2002, real GDP increased at an annualized rate of around 1 percent only. Economy-wide capacity utilization has further declined and the situation on labor markets has worsened. The increase in consumer prices has calmed down somewhat after an acceleration at the beginning of last year. Still, the inflation rate remains surprisingly high against the background of weak economic activity that has already lasted for two years. Monetary policy in the euro area is clearly expansionary. With only about 0.5 percent, the real interest rate is currently quite low by historical standards. Moreover, the nominal interest rate is well below the rate implied by the standard Taylor rule, even when low estimates of the current size of the output gap and the equilibrium real interest rate are employed in the calculation of the rule. Still, monetary policy is probably not too expansionary. According to theory, the equilibrium real interest rate may be substantially below the long-run average real interest rate in situations such as the current one with depressed income and profit expectations. However, these considerations also imply that the ECB should bring the real interest rate back towards the long-run average once the depressing factors will have vanished. The situation of public finances in the euro area deteriorated further in the course of last year, with the aggregated budget in the countries of the euro area approaching a deficit of 2.3 percent of GDP in 2002. The cyclically adjusted budget deficit in the euro area was as high as in 1998, the year immediately before the beginning of the third stage of the Economic and Monetary Union. Whereas most countries have in the meantime complied with the goal of the Stability and Growth Pact to at least balance the budget over the medium term, the budget deficit in Germany, France, Italy and Portugal remained high both in actual and in structural terms. The governments of the three largest countries of the euro area are not likely to switch towards a policy of fiscal consolidation based on cuts in primary spending in 2003 and 2004. Moderate wage settlements would be appropriate in the current cyclical situation. However, wage increases have not slowed down over the past year, and are not expected to do so to any meaningful extent this year and next, reflecting the judgment that labor market rigidities will remain significant over the forecast horizon. Nevertheless, as employment is likely to be slow in responding to a recovery in production, the rise in unit labor costs will decelerate considerably, improving the chances that inflation will fall persistently below 2 percent. The leading indicators suggest that economic activity in the euro area will remain weak in the first half of this year. Under the assumption that the war in the Gulf region is of short duration and that the global political situation calms down afterwards, dampening factors from the Iraq conflict are expected to wane. Impulses from expansionary monetary policy will then increasingly take effect and domestic driving forces will gain the upper hand. We expect real GDP to increase by 1.0 percent and by 2.6 percent in 2003 and 2004, respectively. The situation on the labor market will start to improve towards the end of this year only. Inflation will be moderate over the forecast horizon. In 2004, consumer prices will probably rise by 1.9 percent on average, after 2.2 percent this year.
Keywords: 330; Konjunktur; Konjunkturprognose; Europäische Wirtschafts- und Währungsunion; EU-Staaten